【Student Activity】"Taiwan's SemiconductorTalents Recruitment Activity"has successfully concluded - 國際事務處; Office of International Affairs (國立陽明交通大學, 2023)
[Recruitment Event] October 18, 2023 The "Taiwan's Semiconductor Talents Recruitment Activity" has successfully concluded! 🎉 We'd like to express our gratitude to all the company representatives and students who participated yesterday. This marks the first collaboration between the Office of International Affairs and IDA (Industrial Development Administration) to organize this international semiconductor recruitment event‼️ Through the morning's corporate presentations, students gained a better understanding of various companies. During the afternoon's interview sessions, we hope that students who had the opportunity to interview achieve positive outcomes! 🙏🏻 For those students who couldn't attend this time, don't be disheartened. Follow us on our Facebook and Instagram accounts as we will continue to announce the latest recruitment and student-related activities!✌🏻 Once again, thank you to everyone who participated, and we look forward to seeing you next spring in March 2024! 🤩